Etnobotani Pekarangan di Dusun Kaliurang Barat, Kecamatan Pakem, Sleman-Yogyakarta - Anisatu Z. Wakhidah; Indah A. Sari (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2019)
Homegarden is polyculture garden which located close to house. Due to various plants are possible planted at homegarden so that becoming conservation site is one of the homegarden roles. The homegarden sustainability threat especially at West Kaliurang Village is transition of land functions which has impact in decreasing homegarden plants diversity. This study aims to reveal homegarden plants composition at West Kaliurang and its correlation to homegarden area. Secondly is to explain plant use based on communitty knowledge and to know source of plant acquisition also the origin of plant floristic region. Ethnobotanical data was collected by freelisting interview method that held to common respondent whose homegarde at West Kaliurang. Undentified plants were made herbarium and then identified at laboratory. The study result showed that homegarden plant diversity at West Kaliurang consists of 227 species, 40 Kultivar, and 4 varieties which classified to 80 families. Mostly the homegarden plants found as herb (113 species), shurb (50 species), and tree (203 species). The majority of homegarden plants at West Kaliurang were introduced plants, while just a few were native plants. Keywords : ethnobotany, homegarden plants, west kaliurang, yogyakarta